2016
DOI: 10.1080/10942912.2016.1160922
|View full text |Cite
|
Sign up to set email alerts
|

Sensory profile and preference mapping of cookies enriched with medicinal herbs

Abstract: Running head: Preference mapping of cookies with medicinal herbs ABSTRACTThe sensory profile and acceptance of cookies enriched with medicinal herbs mixture 'Vitalplant', aimed at body weight regulation and metabolism enhancement, were evaluated. Seven cookies were prepared varying the content of powder and extract mixture (0, 2, 4, and 6 g/100 g flour basis, respectively). The descriptors used by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
9
1
Order By: Relevance
“…Pestorić et al. (2017) in their studies reported that the addition of other ingredients such as fat, salt, and sugar in the production of cookies could influence the textural attribute of the formulated cookies. The high textural attribute rating adjudged to cookie produced from wheat flour by the panelists could be as a result of gluten present in the wheat flour as gluten had been known for its textural properties (extensibility).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pestorić et al. (2017) in their studies reported that the addition of other ingredients such as fat, salt, and sugar in the production of cookies could influence the textural attribute of the formulated cookies. The high textural attribute rating adjudged to cookie produced from wheat flour by the panelists could be as a result of gluten present in the wheat flour as gluten had been known for its textural properties (extensibility).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the IPM, the external preference mapping (EPM) utilized the sensory attributes of the products as its scoring pattern. It does so by relating the panelist/consumers scores to the sensory attributes of the products (Pestorić et al., 2017). This method helps in marketing, research, and development of a product as it helps to create products that meet consumers' demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to these four clusters, consumers preferred the Ctrl ice cream the most. Ctrl and C2 were positioned in the warm area where prediction success rate (percentage of cluster mean scores above their mean score) was between 80% and 100% (Pestorić et al ., ). Ctrl and C2 were considered as the samples with the highest relative preference scores across clusters.…”
Section: Resultsmentioning
confidence: 97%
“…[12] Internal and external preference mapping techniques have been implemented in the study of a wide variety of products such as beer, [13] tomatoes, [2] cheeses, [7,14] chocolate milks, [15] filled chocolates, [16] hot dogs, [17] soybean paste, [18] soy-coffee beverages, [3] tropical juice, [19] and cookies enriched with medicinal herbs. [20] The objectives of the present work were: (1) to assess the sensory acceptance of four new strawberry vinegars and also to obtain their sensory profile; (2) to determine which sensory properties drive consumer liking for these products by external preference mapping techniques. Furthermore, we researched consumers' acceptability data using internal preference mapping.…”
Section: Introductionmentioning
confidence: 99%